How is the Driver's Workload Influenced by the Road Environment?. (2017) - Bongiorno, Nicola; Bosurgi, Gaetano; Pellegrino, Orazio; Sollazzo, Giuseppe
Abstract: This paper focuses on the study of the driver's workload while driving on a rural two-lane road with different traffic flows. The aim of the research is to examine a parameter that could be representative of the driving effort, quite sensible to the external factors that cause disturbance to the regular driving activity. To solve this problem, the authors used a specific instrumented vehicle for monitoring some physiological parameters of the driver (as the eye movements and the Galvanic Skin Resistance), referring their values to the road context. The results are very interesting and confirm that knowing the workload is useful to improve the road safety only if it is related to the external context, as well as road geometry, traffic, visibility, etc. Only in this way, the road administrators can deduce proper information to plan and direct accurate and productive upgrade working operations.